On the Positivity of Scattering Operators for Poincaré-Einstein Manifolds (Journal of Mathematical Study, 2021)
In this paper, we mainly study the scattering operators for a Poincaré-Einstein manifold $(X^{n+1}, g_+)$, which define the fractional GJMS operators $P_{2γ}$ of order $2γ$ for $0